Pengaruh Persediaan dan Distribusi terhadap Efisiensi Supply Chain Management pada Produk IWF NON-PRIME di PT Krakatau Baja Konstruksi - Muqoyyimah Muqoyyimah; Siti Fatimah; Ibnu Falekh; Rizky Romadona (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research aims to determine the influence of inventory and distribution on supply chain management for IWF products at PT Krakatau Baja Kontruksi (KBK). In this research, researchers used descriptive research using a qualitative approach. The data obtained comes from internal data from the KBK company for the period September to October 2024. From the data obtained, data on the number of stock items in the warehouse in September was 46,339 units with the total number of deliveries amounting to 40,090 items, while in October the number of stock items in the warehouse is 43,538 cigarettes with the number of deliveries being 39,115 cigarettes with a total inventory of 89,877 stems and the total number of shipments was 79,205 stems in the period from September to October. Based on the data obtained, it can be concluded that the inventory and distribution of IWF products has an influence on the efficiency of Supply Chain Management at PT Krakatau Baja Kontruksi. Because inventory and distribution are increasingly optimal, the main goal of Supply Chain Management has been achieved.